The extent to which the principles of human rights are contained in secondary schools’ Arabic language textbooks in the Kingdom of Saudi Arabia: emphasis on how they are taught and internalized by the students - al madani, Feras; Rawash, Fouad (Wudpecker Journals, 2014)
The first aim of this study is to investigate the principles of human rights in the Arabic language textbooks for the selected secondary schools in the northern border in the Kingdom of Saudi Arabia. Secondly, to analyze these principles through method and strategies they were taught and how the students internalize them. In order to achieve these purposes, 12 Arabic textbooks were analyzed using content analysis, 64 Arabic teachers, and 266 students were administered a survey questionnaire. The results of the study showed that the Arabic textbooks covered the principles of human rights well, except few of them, the teachers partly explained these principles and that the students averagely internalized the principles. According to these results, it was recommended that the Arabic language curriculum needs to be reviewed to explicitly support the principles of human rights and the in-service training programs were to be provided for Arabic teachers to treat the neglected parts related to the principles of human rights.